Estudo das tensões residuais do ferro fundido em um componente pantográfico de semeadora para agricultura de precisão - Kach, Sirnei César (2014)
This work takes for finality main Magma carries out a study through the use of the software of numerical simulation, for checking of the residual tensions provoked by the process of fusing, in the support of the pantograph of the plant machines used in the agriculture of precision. This necessity appears in function of break of pieces in fulfilled row of seats tests previously in the phase of development of the prototype, signaling the possibility of a possible weakening of the component one in function of the excess of concentration of residual tensions in the item or hard-working efforts. The used methodology was through the realization of simulations with use of the software of numerical simulation, that it analyses two proposed for fusing of the pieces. The first one has three pieces for mold and on Monday with two pieces for mold. This profile of the distribution of pieces in the mold has a tendency to provoke a behavior differentiated between two proposals and in spite of the fact that that checks which presents the best result, in other words, less concentration of residual tensions formed during the process of fusing. From the fulfilled numerical simulation, where was considered the main variables, at pieces disposal in the mold, temperature of desmoldagem what respected the phase eutetóide of 730ºC, satisfactory results were obtained since the concentration of low residual tensions, concentrating around 50MPa and the item for his time projected to support up to 320 MPa of hard-working efforts. The results prove what even taking different quantities of pieces as a mold, consequently you distinguish of volume from emptied liquid metal, there were no variations in the concentration of the residual tensions in the piece that could in some form compromise the performance in his application. one concludes so that the concentration of residual tensions with maximum of 50MPa, does not affect his performance in function of the demand of efforts suffered by the piece in the system pantograph of the plant machines. Being able in this way, to be used with security and guarantee of the product will attend the demand of efforts and demands of load for which was projected.